Significance of reactive oxygen species and oxidative stress in carcinogenesis - Jopkiewicz, Sylwia Paulina (Journal of Education, Health and Sport, 2019)
Introduction and aim.Reactive oxygen species and increased oxidative stress cause a series of disorders in the metabolism of the cell. Initiate adverse changes to the structure of DNA, lipids and proteins. The purpose of this article is to introduce the concept of oxidative stress and reactive oxygen species and to present their contribution to the formation and development of precancerous and cancerous.Description of knowledge.The process of oxidation damage of DNA molecules nitrogen bases, contributes to the rupture of DNA strands and the formation of adducts. Lipid peroxidation cause damage to membranes of cytoplasmic and mitochondrial which causes unfavorable changes in their physical properties. The end products of this process show mutagenic and carcinogenic. Oxidation of proteins leading to changes in their structure and the presence of structurally abnormal protein, which is the main regulator of the cell can cause the initiation of the neoplastic process. The emergence of mutations in the DNA is a critical point in the process of carcinogenesis.Conclusions.Oxidative stress and the effects of reactive oxygen species is one of the reasons for the initiation and development of cancer. Permanent changes in the structure of DNA, lipids and proteins leading to the loss of their biological functions and following the development of lesions.